Genetic and structural characterization of the human mitochondrial inner membrane translocase - Bauer, Matthias F.; Gempel, Klaus; Reichert, Andreas; Rappold, Gudrun; Lichtner, Peter; Gerbitz, Klaus-Dieter; Neupert, Walter; Brunner, Michael; Hofmann, Sabine (Journal of molecular biology, 1999)
Translocation of nuclear-encoded mitochondrial preproteins is mediated by translocases in the outer and inner membranes. In the yeast Saccharomyces cerevisiae, translocation of preproteins into the matrix requires the membrane proteins Tim23, Tim17 and Tim44, which drive translocation in cooperation with mtHsp70 and its co-chaperone Mge1p. We have cloned and functionally analyzed the human homologues of Tim17, Tim23 and Tim44. In contrast to yeast, two TIM17 genes were found to be expressed in humans. TIM44, TIM23 and TIM17a genes were mapped to chromosomes 19p13.2-p13.3, 10q11.21-q11.23 and 1q32. The TIM17b gene mapped to Xp11.23, near the fusion point where an autosomal region was proposed to have been added to the “ancient” part of the X chromosome about 80-130 MY ago. The primary sequences of the two proteins, hTim17a and hTim17b, are essentially identical, significant differences being restricted to their C termini. They are ubiquitously expressed in fetal and adult tissues, and both show expression levels comparable to that of hTim23. Biochemical characterization of the human Tim components revealed that hTim44 is localized in the matrix and, in contrast to yeast, only loosely associated with the inner membrane. hTim23 is organized into two distinct complexes in the inner membrane, one containing hTim17a and one containing hTim17b. Both TIM complexes display a native molecular mass of 110 kDa. We suggest that the structural organization of TIM23·17 preprotein translocases is conserved from low to high eukaryotes.